Xanthan gum − mucin complexation: Molecular interactions, thermodynamics, and rheological analysis. (May 2021) - Ahmad, Mehraj; Ritzoulis, Christos; Chen, Jianshe; Meigui, Huang; Bushra, Rani; Jin, Yongcan; Xiao, Huining
Abstract: Texture perception, astringency phenomena, and oral sensation are directly influenced by molecular interactions. This study systematically characterizes the diverse array of molecular interactions in a binary model system comprising of mucin, the major viscosity enhancer of biological fluids, and xanthan gum, a major food hydrocolloid, at a pH range of 1–7. Coexistence of xanthan gum and mucin at 1:2 ratio (w/w) under acidic pH results in phase separation, as evidenced by the formation of visible aggregates. ζ-Potential data rule out any relevant electrostatic interactions. Fluorimetry analysis points to the existence of two distant binding regimes of mucin, manifesting at low ( y 1 ) and high ( y 2 ) xanthan gum concentrations, corroborating a pH-independent two-step binding mechanism. Enthalpy-dominated (Δ H° < 0) interaction occur at pH 7, whilst, entropy-driven (Δ S° > 0) interactions (classical hydrophobic forces) stabilize both transient and static complexes at pH 3. Both macromolecules interact spontaneously (Δ G° < 0) at the two pH values. Based on rheological data, the macromolecular interaction proves to be less dependent on the mucin to xanthan gum weight ratios. Nevertheless, the partial substitution of mucin with xanthan gum leads to enhanced viscoelasticity ( G' > G" ) and increased relaxation times (λ). Furthermore, the xanthan gum inclusion in mucin systems at a 5:5 (w/w) ratio elevates the apparent viscosity ( η ) ≥ 45-fold (21.59 Pa s) and ≥70-fold (33.52 Pa s) in comparison with mucin (0.46 − 0.48 Pa s) at pH 3 and pH 7, respectively. The findings of this study highlight the physicochemical basis of designing dysphagia diets, modulating food functionality, and tailoring the organoleptic properties of food systems. Graphical abstract: Image 1 Highlights: Xanthan gum−mucin complexation was investigated as a function of pH. Two binding regimes of mucin, manifest at low and high xanthan gum concentrations. Enthalpy-dominated (Δ H° < 0) non-electrostatic interactions occur at pH 7. Entropy-driven (Δ S° > 0) hydrophobic interactions stabilize binary complex at pH 3. Non-transient and transient interactions had lifespans of 0.1–2 s.